Andrzej Mostowski and foundational studies - Mostowski, Andrzej; Ehrenfeucht, Andrzej; Marek, V. W. (V. Wiktor), 1943-; Srebrny, Marian, 1947- (Ios Press, 2008)
Andrzej Mostowski was one of the leading 20th century logicians. This volume examines his legacy, devoted both to his scientific heritage and to the memory of him as a great researcher, teacher, organizer of science and person. It includes the bibliography of Mostowski's writings.